Thermodynamic irreversibility in mixed convective MHD flow of radiative hybrid nanofluids with couple-stress effects - Pungja Mushahary; Surender Ontela (JCIS Open)
The paper presents the analysis of the mixed convective flow of magnetohydrodynamic (MHD) couple stress hybrid nanofluid (CSHNF) in a porous vertical channel. The system is equipped with quadratic thermal radiation, an external heat source, and a uniform magnetic field. The study applies to advanced microchannel systems, microelectromechanical systems (MEMS) development, and lab-on-a-chip (LOC) technology. The irreversibility analysis of the system is based on the entropy generation number and the Bejan number. The considered hybrid nanofluid is processed by mixing multi-walled carbon nanotubes (MWCNT) and silver (Ag) nanoparticles in a base fluid of ethylene glycol (C2H6O2). The flow is induced by the pressure gradient force and the buoyancy force modeled through the Boussinesq approximation, characterizing it as mixed convective flow. The governing equations are nondimensionalized by applying relevant dimensionless parameters and solved using the homotopy analysis method (HAM). The obtained results are validated through existing results, ensuring consistency and reliability with established findings. The effects of different significant parameters on the velocity and temperature profiles and entropy generation rate are scrutinized. The analysis reveals that entropy generation degrades up to 19% and 1% for the concentration and Darcy number range of 0≤ϕi≤0.02 and 0.1≤Da≤0.9. In contrast, it enhances up to 25% and 90% for thermal radiation and convective conditions for the range 0≤RD≤0.1 and 0.3≤Bii≤0.5. The heat transfer rate was reduced by about 0.5% and 17% at the parameter range 0≤ϕi≤0.02 and 0.1≤QT≤0.2.